The androgen model of suicide completion - Lenz, Bernd; Röther, Mareike; Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Tektas, Ozan Y.; Kornhuber, Johannes (Progress in Neurobiology, 2019)
Suicide is a devastating public health issue that imposes severe psychological, social, and economic burdens not only for the individuals but also for their relatives, friends, clinicians, and the general public. Among the different suicidal behaviors, suicide completion is the worst and the most relevant outcome. The knowledge of biological etiopathological mechanisms involved in suicide completion is limited. Hitherto, no objective markers, either alone or in combination, can reliably predict who will complete a suicide. However, such parameters are strongly needed to establish and optimize prediction and prevention. We introduce here a novel ideation-to-completion framework in suicide research and discuss the problems of studies aiming at identifying and validating clinically useful markers. The male gender is a specific risk factor for suicide, which suggests that androgen effects are implicated in the transition from suicidal ideation to suicide completion. We present multiple lines of direct and indirect evidence showing that both an increased prenatal androgen load (with subsequent permanent neuroadaptations) and increased adult androgen activity are involved in suicide completion. We also review data arguing that modifiable maternal behavioral traits during pregnancy contribute to the offspring's prenatal androgen load and increase the risk for suicide completion later in life. We conclude that in utero androgen exposure and adult androgen levels facilitate suicide completion in an synergistic manner. The androgen model of suicide completion provides the basis for the development of novel predictive and preventive strategies in the future.
EVALuna2:211632